2014
DOI: 10.1213/ane.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation Reduces Mechanical Hyperalgesia and Restores Physical Activity Levels in Animals with Noninflammatory Muscle Pain in a Frequency-Dependent Manner

Abstract: The current study shows that higher frequencies of SCS (60 and 100 Hz) significantly reduce mechanical hyperalgesia of the paw and muscle in an animal model of noninflammatory muscle pain, and 60 Hz SCS restores physical activity levels of animals, not 4 Hz.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 96 publications
(107 reference statements)
0
13
2
Order By: Relevance
“…There was no effect of SCS or proglumide on activity levels, which is in contrast to our prior study . The lack of SCS effect on activity levels may be related to the duration of stimulation since our prior studies showing an improvement in activity were done with much longer stimulation (six hours) , and/or over multiple days (four days–three months) .…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…There was no effect of SCS or proglumide on activity levels, which is in contrast to our prior study . The lack of SCS effect on activity levels may be related to the duration of stimulation since our prior studies showing an improvement in activity were done with much longer stimulation (six hours) , and/or over multiple days (four days–three months) .…”
Section: Discussioncontrasting
confidence: 98%
“…The number of rearing and grooming behaviors were counted manually from the stored videotapes. We previously show nerve injury reduces distance traveled, number of crossings, and rearing which we interpret as reduced function (28,43). SCS returns these behaviors toward normal (28,43).…”
Section: Behavior Testsmentioning
confidence: 52%
“…Another limitation was that the patients with early response (within 10 min) to the SCS were included in this study, excluding those with delayed or carry‐over effect, which may not represent the true sample of all the patients with SCS. This was potentially unavoidable due to required study methods and due to reported variations in the carry‐over effect of SCS . Nonetheless, our study provides insights into the mechanism of SCS and cortical connectivity.…”
Section: Discussionmentioning
confidence: 97%
“…Although a review showed little evidence of SCS improving daily activities in humans, it has been reported that SCS restored daily physical activity in animals . The effect of SCS on daily activities is therefore a secondary objective, whereas pain relief forms the primary objective in clinical research .…”
Section: Discussionmentioning
confidence: 99%